The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.cjco.2020.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History and Treatment of Cardiac Implantable Electronic Device Associated Pneumothorax—A 10-Year Single-Centre Experience

Abstract: Background Pneumothorax is a common complication of cardiac implantable electronic device (CIED) procedures. There is a paucity of data on the natural history and management of a CIED-associated pneumothorax. Methods This is a single-centre retrospective study of all consecutive patients with a CIED-associated pneumothorax between March 2010 and March 2020. Pneumothorax size was determined on all chest x-rays after device implantation and before chest tube insertion (if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Caudal imaging may also allow for rationalization in routine use of CXR following CIED insertion. In a recent review of the yield of CXR after CIED insertion, pneumothoraces were found to occur in 1.9% cases 21 . Given the markedly lower incidence of pneumothorax associated with caudal imaging in our study, it may be suitable to consider a more tailored approach to post‐procedural CXR, for instance only in the setting of operator‐reported access challenges or patient‐reported symptoms.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Caudal imaging may also allow for rationalization in routine use of CXR following CIED insertion. In a recent review of the yield of CXR after CIED insertion, pneumothoraces were found to occur in 1.9% cases 21 . Given the markedly lower incidence of pneumothorax associated with caudal imaging in our study, it may be suitable to consider a more tailored approach to post‐procedural CXR, for instance only in the setting of operator‐reported access challenges or patient‐reported symptoms.…”
Section: Discussionmentioning
confidence: 69%
“…In a recent review of the yield of CXR after CIED insertion, pneumothoraces were found to occur in 1.9% cases. 21 Given the markedly lower incidence of pneumothorax associated with caudal imaging in our study, it may be suitable to consider a more tailored approach to post-procedural CXR, for instance only in the setting of operator-reported access challenges or patient-reported symptoms. One limitation of the caudal fluoroscopic (and other oblique) view is the potential for increased radiation scatter which results in greater radiation exposure to the proceduralist.…”
Section: Puncture Of the Extrathoracic Subclavian Vein (Subclavian Ve...mentioning
confidence: 88%
“…A similar result was reported by Faruqi et al, and the mean pain scores for simple aspiration and intercostal tube drainage were 1.6 and 4.0 respectively [ 17 ]. Moreover, the lack of indwelling catheter not only alleviated the irritable sensation that occurred owning to the presence of a foreign body object inside the body, which enabled patients to mobilize freely without limitation or fear of tube dislodgement, but also reduced the clinical burden of tube care on the nursing stuff and the medical costs [ 23 ]. Finally, no complication occurred in patients who underwent vacuum bottle plus non-tunneled catheter drainage in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A patient can manifest signs and symptoms during the procedure or up to 72 hours after implantation ( 20 ). Every patient should receive a chest x-ray within 4 h post-procedure ( 30 ). Patients discharged from the hospital shortly after outpatient procedures should remain in contact with the CIED center ( 17 ).…”
Section: Discussionmentioning
confidence: 99%